El estudio del estrés. Un modelo para armar - Ramírez Velásquez, Josefina Amparo (Estudios de Antropología Biológica, 2010)
In this work it is described, in a synthetic way, the path concept of stress followed in its construction like object of anthropological study, highlighting in a particular way the construction of a description model and analysis generated starting from relating theoretical proposals and empiric data. The nodal intention is to show the important relationship that has an investigation position that keeps logic and it rhymes with the conceptualization and with the central variables that are in game.